PENGARUH METODE PEMBELAJARAN FUN LEARNING TERHADAP KETERAMPILAN GERAK DASAR MOTORIK PESERTA DIDIK - Firman Dwi Nugraha; Aref Vai; Kristi Agust (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to identify the influence of the fun learning teaching method on the fundamental motor skills of fourth-grade students at SDN 77 Pekanbaru. The research employed an experimental method with a pre-test and post-test design. Data were collected using the Test of Gross Motor Development-2 (TGMD-2) before and after implementing the fun learning method over 10 sessions. The analysis results indicate a significant improvement in students' motor skills, with the average post-test scores being higher than the pre-test scores. Additionally, this method enhanced students' activeness, enthusiasm, and creativity during the learning process. Statistical tests showed a significance value (0.001) < 0.05, supporting the acceptance of the alternative hypothesis (Ha). This study concludes that the fun learning method effectively improves students' motor skills and can serve as an innovative teaching alternative. Recommendations are provided for teachers, schools, students, and researchers to optimize the application of this method in education.